INVENTORY MANAGEMENT ANALYSIS FOR LIGHT STEEL ASSEMBLY OPTIMIZATION IN CV. NIRA JAYA ABADI, EAST LAMPUNG - SANDORA, PUTRI; FAUZI, FAUZI (SOCIAL : Jurnal Inovasi Pendidikan IPS, 2023)
Business competition in Indonesia is getting tighter along with the increasing number of entrepreneurs and new companies. One of the important sectors is the construction industry, especially the roofs of buildings that function as protection from weather elements and falling objects. The importance of raw material inventory for smooth production is crucial, because it affects the production process and operational costs. This study aims to analyze the inventory management of raw materials in meeting the demand for light steel assembly in CV. Nira Jaya Abadi in Way Jepara District, East Lampung. The data collection methods used are documentation and interviews. The results of the study show that the management of raw material inventory in CV. Nira Jaya Abadi is not yet optimal in 2023. Using the Economic Order Quantity (EOQ) method, it was found that the number of economical purchases of raw materials was 3,623 units, while the average purchase made by the company was only 1,617 units. This results in a higher frequency of purchases, which is 12 times a year, compared to the optimal frequency of 5 times. As a result, the cost of ordering and inventory of raw materials increased, with inventory costs reaching IDR 19,440,670, while the optimal cost according to the EOQ calculation was IDR 17,065,510.5. This inefficiency causes the company to bear additional costs as well as the risk of damage to raw materials. ABSTRAKPersaingan bisnis di Indonesia semakin ketat seiring dengan semakin banyaknya wirausahawan dan perusahaan baru. Salah satu sektor yang penting adalah industri konstruksi khususnya atap bangunan yang berfungsi sebagai pelindung dari unsur cuaca dan benda jatuh. Pentingnya persediaan bahan baku untuk kelancaran produksi sangatlah penting, karena mempengaruhi proses produksi dan biaya operasional. Penelitian ini bertujuan untuk menganalisis manajemen persediaan bahan baku dalam memenuhi permintaan perakitan baja ringan di CV. Nira Jaya Abadi di Kabupaten Way Jepara, Lampung Timur. Metode pengumpulan data yang digunakan adalah dokumentasi dan wawancara. Hasil penelitian menunjukkan bahwa pengelolaan persediaan bahan baku di CV. Nira Jaya Abadi belum optimal pada tahun 2023. Dengan menggunakan metode Economic Order Quantity (EOQ), diketahui jumlah pembelian bahan baku yang ekonomis sebanyak 3.623 unit, sedangkan rata-rata pembelian yang dilakukan perseroan hanya 1.617 unit. Hal ini mengakibatkan frekuensi pembelian lebih tinggi yaitu 12 kali dalam setahun dibandingkan frekuensi optimal yaitu 5 kali. Akibatnya biaya pemesanan dan persediaan bahan baku meningkat, dengan biaya persediaan mencapai Rp19.440.670, sedangkan biaya optimal menurut perhitungan EOQ adalah Rp17.065.510,5. Inefisiensi ini menyebabkan perusahaan menanggung biaya tambahan serta risiko kerusakan bahan baku.